2021
DOI: 10.3390/jpm11121346
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal Variation and Severity of Acute Abdomen in Japan: A Nine-Year Retrospective Analysis

Abstract: The seasonal incidence of acute abdomens, such as appendicitis, is reportedly more common in summer but is reported less frequently in Asia. Additionally, seasonal variations in the severity of acute abdomens have been evaluated insufficiently. This study evaluated the seasonal variations in the incidence and severity of acute abdomens in Japan. This retrospective observational study used a multicenter database containing data from 42 acute hospitals in Japan. We included all patients diagnosed with acute appe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
1
0
3

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 25 publications
2
1
0
3
Order By: Relevance
“…Our analysis, in parallel with studies published in the literature, showed an increased number of intraoperative findings (appendicular abscess, peritonitis and appendicular perforation) as well as higher staging of acute appendicitis on pathological examinations and higher inflammatory indices on blood tests during the pandemic (28,36). It has been described that patients presenting to the surgical department more than 1 day after the onset of signs and symptoms are at a higher risk of suffering from perforated appendicitis (43,44).…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Our analysis, in parallel with studies published in the literature, showed an increased number of intraoperative findings (appendicular abscess, peritonitis and appendicular perforation) as well as higher staging of acute appendicitis on pathological examinations and higher inflammatory indices on blood tests during the pandemic (28,36). It has been described that patients presenting to the surgical department more than 1 day after the onset of signs and symptoms are at a higher risk of suffering from perforated appendicitis (43,44).…”
Section: Discussionsupporting
confidence: 81%
“…Differently, median age, sex and incidence did not show significant differences during the different periods. Due to the period comparability, without seasonal or demographic differences between the groups, we did not observe variation in incidence, as similarly reported by numerous studies (36,37).…”
Section: Discussionsupporting
confidence: 78%
“…(15) Se destaca que la evaluación fisiológica no debe ser el único factor evaluado para predicción de mortalidad, ya que esto puede subestimar o sobreestimar las probabilidades de mortalidad, tal es el motivo que se incluyan a la evaluación otros parámetros demográficos como la edad, sexo o comorbilidades, aumentando la capacidad de predicción entre un 5-6 %. (10,14,15) Yoshimoto et al (16) en su estudio sobre asociación de enfermedades intraabdominales con el clima, describe brevemente que las variaciones estacionales no se relacionan con la gravedad de los pacientes. En este sentido, si se describe la importancia de incluir las comorbilidades a un modelo de predicción de mortalidad, cuyo modelo https://doi.org/10.56294/saludcyt2022209 3 Verdesoto Herrera FE, et al base utilizado fue la escala SOFA sin evaluación de los parámetros cardiovascular y respiratorio, concluyendo que los adultos mayores, por puntuación, son más propensos a desarrollar sepsis asociada a colecistitis aguda y colangitis aguda.…”
Section: Resultsunclassified
“…(4) Otros autores indican como otras causas de sepsis de origen abdominal la apendicitis, colecistitis y diverticulitis. (6,13,16) Asimismo, autores concuerdan en que los puntajes evaluados por escala SOFA y APACHE II son semejantes y adecuados para la predicción de mortalidad en pacientes con shock séptico abdominal, esto debido a la disponibilidad de variables evaluadas en el servicio de emergencia y cuidados intensivos. (1,20) Otra escala validada, que presenta una alta sensibilidad al predecir mortalidad asociadas a shock séptico de origen abdominales es el sistema SAPS, con una sensibilidad del 88 % y especificidad del 71 %, sin embargo, en países como Perú son poco utilizados.…”
Section: Discussionunclassified
See 1 more Smart Citation